Investigation of interaction between biological fluid crystallogenic activity and intensity of experimental infection by Trichinella spiralis - A. K. Martusevich; O. B. Zhdanova (Российский паразитологический журнал)
Urine dehydration structurization at experimental trichinellosis of rats is studied. In 4 weeks after exposure rats urine was analyzed with biocrystallomics methods. It was stated, that urine crystallogenic properties changes according to intensity of infection.